Annual Report of the Ministry of Health County Caroni for the year ending 31st day of December 1986 - Trinidad and Tobago. Caroni County Health Team (My University, 1987)
This report notes that the year 1986 is one which gains made in the previous years were consolidated. Throughout the year, emphasis was laid on the optimum use of resources involving manpower and time.
Keywords: County Health